2012
DOI: 10.1090/s0894-0347-2012-00735-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic derivation of Ginzburg-Landau theory

Abstract: We give the first rigorous derivation of the celebrated Ginzburg-Landau (GL) theory, starting from the microscopic Bardeen-Cooper-Schrieffer (BCS) model. Close to the critical temperature, GL arises as an effective theory on the macroscopic scale. The relevant scaling limit is semiclassical in nature, and semiclassical analysis, with minimal regularity assumptions, plays an important part in our proof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
223
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(230 citation statements)
references
References 23 publications
7
223
0
Order By: Relevance
“…Let us discuss the similarities and differences between this paper and our previous paper [6]. In [6] it was shown that for…”
Section: Lemma 25 the Critical Value D C Is Uniquely Characterized mentioning
confidence: 69%
See 3 more Smart Citations
“…Let us discuss the similarities and differences between this paper and our previous paper [6]. In [6] it was shown that for…”
Section: Lemma 25 the Critical Value D C Is Uniquely Characterized mentioning
confidence: 69%
“…In [6] this was shown for D > 0, but in [8] it was remarked that the same proof works even for D ≤ 0, provided the normalization of α * is changed accordingly. …”
Section: Lemma 25 the Critical Value D C Is Uniquely Characterized mentioning
confidence: 87%
See 2 more Smart Citations
“…It can be derived from the microscopic theory due to Bardeen, Cooper and Schrieffer [8,10]. Stationary states of superconductors occupying (for simplicity) the plane R 2 , are described by pairs (ψ, A), where ψ : R 2 → C is the order parameter and A : R 2 → R 2 is the magnetic potential.…”
Section: Introductionmentioning
confidence: 99%